2018
DOI: 10.1002/adbi.201800030
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Neuronal Networking via Removable Alginate Masks

Abstract: The neuron patterning method has been applied to cultured neuronal networks to achieve better reproducibility and various experimental conditions in brain research. However, as models of dynamic environments, conventional patterned neural networks having an unalterable structure formed by a preprogrammed substrate have limitations, such as replicating the changes in the physical structure of networks in vivo. This study presents a novel culture technique that can control the location of the neuronal cell bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Furthermore, this is especially true for complex and highly dynamic tissues such as those formed from 3D neuronal networks. While these tissues have been shown to have high degrees of connectivity, synchrony, and bursting behaviors [6][7][8][9] , they consistently show high variability in their resulting firing patterns. Furthermore, while Hebbian plasticity has been shown to be activated in in-vitro cultures to affect the dynamic of neuronal network at a cellular level 10 , achieving control of tissue-wide modulation of the directionality of neuronal activity has yet to be shown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this is especially true for complex and highly dynamic tissues such as those formed from 3D neuronal networks. While these tissues have been shown to have high degrees of connectivity, synchrony, and bursting behaviors [6][7][8][9] , they consistently show high variability in their resulting firing patterns. Furthermore, while Hebbian plasticity has been shown to be activated in in-vitro cultures to affect the dynamic of neuronal network at a cellular level 10 , achieving control of tissue-wide modulation of the directionality of neuronal activity has yet to be shown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown varying degrees of emerging phenomena that are correlated to neuronal plastic events that would imply “learning” or “memory storage” in neural circuits 9 13 These varying degrees extend from neural mechanisms that regulate potentiation to feedback mechanisms with respect to associations to stimulation. Currently, in-vitro micro electrode array (MEA) systems have aimed to study the effects of stimulation protocols in the resulting network dynamics for the past 30 years 13 19 . While some of these studies have induced transient changes in the recorded signals, most have focused on changes of number of action potentials in mature primary neurons and in learning as a result of feedback to strengthen associations to the stimulation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Many surface modification techniques have been developed for patterning culture substrates with proteins, polymers, and adhesion promoting molecules. Surface coatings can be patterned with the help of photolithography, , microcontact printing with poly­(dimethylsiloxane) (PDMS) , or polyolefin stamps, photobleaching-based cross-linking, masked plasma-etching, UV-based photoscission, laser-interference ablation, polymer brushes, polymer and biomolecule printing, ,, and many similar methods. However, despite the wide range of available techniques, they all present important shortcomings.…”
Section: Introductionmentioning
confidence: 99%